2018
DOI: 10.1007/s12031-018-1064-8
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Analysis of Cerebral Cortex Extracts from Sus scrofa with Induced Hemorrhagic Stroke

Abstract: Cerebrovascular diseases, including stroke and micro stroke, are the main causes of death in contemporary society. Hemorrhagic stroke is the fast emerging defficiency in the brain function resulting from disturbance of blood supply to the brain caused by the rapture of blood vessels (Lopez et al. in Proteomics Clin Appl 6:190-200, 2012). The influence of a model hemorrhagic stroke on white pigs with the change in the protein profile of their cortical samples 24 h and 2 months after the stroke was examined usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 21 publications
1
11
0
Order By: Relevance
“…Although there are no previous studies on the proteome of human brain following ICH, a study in a pig model of ICH showed differences in proteomic expression of whole tissue at 24 h and at 60 days compared to controls 38 . Another study in a rat model of acute ICH showed differential protein expression 39 , as did a tissue proteomic study of collagenase-induced ICH in rats at 2 days post-ICH 40 .…”
Section: Discussionmentioning
confidence: 92%
“…Although there are no previous studies on the proteome of human brain following ICH, a study in a pig model of ICH showed differences in proteomic expression of whole tissue at 24 h and at 60 days compared to controls 38 . Another study in a rat model of acute ICH showed differential protein expression 39 , as did a tissue proteomic study of collagenase-induced ICH in rats at 2 days post-ICH 40 .…”
Section: Discussionmentioning
confidence: 92%
“…ICH releases blood cells and their breakdown products into the brain parenchyma. This release subsequently damages neurons and neural tissues. In addition to the initial injury and mass effects, processes associated with brain injury during ICH include red blood cell (RBC) lysis, which results in the release of free hemoglobin (Hb). , Free Hb is unstable and undergoes unchecked auto-oxidation to release hemin and globin chains. While the amino acids of globin chains are recycled for protein synthesis, the fate of hemin may be converted into biliverdin, which can act as an antioxidant, or into redox-active iron, which can be reused for Hb synthesis or as free hemin.…”
mentioning
confidence: 99%
“…Further autologous venous blood (from the ear vein of the same pig, 300 mkl) was injected into the damaged area ( Figure 1 a). This surgery allowed us to obtain a reproducible model of intracerebral hemorrhage with necessary precision, as was described in [ 9 ]. Sham surgery was performed without damaging the brain structures.…”
Section: Methodsmentioning
confidence: 99%